A new chemo-mechanical model of damage in concrete under sulfate attack. (15th July 2016) - Chen, Jian-kang; Qian, Chen; Song, Hui
Graphical abstract: The characteristic time tp related chemical reaction rate approximately is the inflection point of damage evolution. Highlights: Damage evolution in concrete under sulfate attack is derived considering chemical reaction rate. The characteristic time of chemical reaction represents inflection point of damage evolution. Damage nucleation is due to tensile failure at the surface of pores by delayed ettringite. Abstract: Damage evolution is detected via the degradation of modulus of concrete immersed in sulfate solution. The mechanism of the damage is investigated by using SEM method, and it is proved that the internal expansion stress induced by delayed ettringite leads to the nucleation of micro-cracks. The criterion of damage nucleation is proposed in terms of the tension strength of concrete. The differential equation with respect to the internal expansion stress is derived by virtue of chemical reaction rate on delayed ettringite formation, and a new chemo-mechanical model of corrosion damage in concrete under sulfate attack is then proposed.